Pengaruh Gaya Kepemimpinan dan Lingkungan Kerja terhadap Kepuasan Kerja dan Kinerja Karyawan (Studi Pada Karyawan PT. Wenang Cemerlang Press) - Tommy Waworundeng; William A. Areros; Wehelmina Rumawas (Universitas Sam Ratulangi, 2021)
The organization is a complex unit that allocates human resources to achieve goals. One of the goals of the organization is to improve the performance of employees to support the performance of the organization so that if the organization achieves the goals set, it can be said that the organization is effective. This study aims to analyze the influence of leadership style and work environment on job satisfaction and employee performance. The sample in this study were employees of PT. Wenang Cemerlang Press. Data was obtained by using a questionnaire to 79 respondents. Data analysis using the Structural Equation Model with the help of SmartPLS 3 software. The results show that leadership style has a positive and significant effect on employee performance, leadership style has a positive and significant effect on job satisfaction, the work environment has a positive and significant effect on job satisfaction, the work environment has a positive effect. and significant effect on employee performance, and job satisfaction has a positive and significant effect on employee performance.